An application of neural network for harmonic detection in active filter - Pecharanin, N.; Sone, M.; Mitsui, H. (IEEE International Conference on Neural Networks, 1994, 1994)
This paper describes the method which uses neural networks for the harmonic detection process in an active filter. Originally, Fourier transformation is used to analyze the distorted wave from the power line and a low-pass filter is used to eliminate the fundamental wave before each harmonic component is detected. Due to these complicated processes, the behavior of the active filter is delayed such that it is difficult to compensate the harmonics in real time. In order to improve the processing speed and simplify the harmonic detection process, a neural network is used to detect the harmonics in the distorted wave instead of Fourier transformation and low-pass filter. The authors simulated the distorted wave including 3rd, 5th and 7th harmonics and used a neural network to recognize each harmonic. The results shows that a neural network enable to detect each harmonic effectively.< >